PERAN ORANG TUA DALAM MENINGKATKAN KEDISPILINAN ANAK (Studi Kasus di Lingkungan Mensawang Kelurahan Dusun Bangko ) - Alatas, uying Hapid; AS, Fatimah; Syukurman, M.; Afrinovera, Afrinovera (Jendela PLS, 2024)
This research is motivated by the attitude of parents not caring about children's discipline. Where, it was found that some parents pay less attention to their children's discipline problems and actually make children late to school on time, the busyness of parents, especially mothers as housewives, first doing housework so that children are late to come on time, the busyness of parents, especially mothers as housewives, first doing housework, so that children are late to come to school. The purpose of this study was to find out what parents do and what obstacles parents face in improving discipline towards children in the Mensawang Environment, Bangko Hamlet. This type of research is qualitative research using a case study approach. The number of respondents in this study was 5 parents of children who attended elementary school. Data collection techniques used observation techniques (Observation), interviews, and documentation. While the data analysis technique is by conducting data reduction, data display (data presentation), conclusions (verification). From the results of the data analysis, it can be concluded that some things that parents do to make children disciplined are to be role models for their children, namely by getting children used to doing disciplined activities such as brushing their teeth before going to bed, reading prayers and making the bed, besides that parents also give praise or give awards in the form of gifts for their children who can get used to these disciplined activities. Families, especially parents who live in the Mensawang Environment, Bangko Hamlet, try to shape their children's disciplined character in everyday life by getting children used to it from an early age so that they can apply disciplined behavior in various fields from the smallest things by providing real examples for their children. In its implementation, there are several obstacles or problems that are often encountered, including economic factors so that parents are busy with work, technological advances that affect children's activities and playmates or the child's living environment. For that, as parents, we must be able to work around it so that this does not become an obstacle to increasing children's discipline. By instilling discipline from an early age, children will understand and not be negligent in applying discipline wherever they are. Facing the development of the era, parents should be able to understand and follow the development, so that parents can apply discipline in accordance with the development of the era. .